Application of poly(2-hydroxyethyl methacrylate) hydrogel disks for the immobilization of three different microalgal species - Eroglu, E.; Wijihastuti, R.; Grenik, E.; Vadiveloo, A.; Moheimani, N.; Lou, Xia (Wiley, 2018)
BACKGROUND: Algal growth on solid surfaces confers the advantage of combining the algal harvesting and bioprocessing steps at a single stage, in addition to the easier handling of the immobilized cells that occupy a reduced amount of space. The current work employed the application of macroporous poly(2-hydroxyethyl methacrylate) (PHEMA) hydrogel disks as a water-insoluble, non-toxic and recyclable immobilization matrix for different microalgal strains (Nannochloropsis sp., Dunaliella salina, and Botryococcus braunii) that offer value-added products for various commercial applications. RESULTS: The study demonstrated the effect of variations in the surface characteristics of the algal strains and hydrogel surfaces on the immobilization efficiencies. Gelatin was further used to modify PHEMA hydrogels to achieve higher bioaffinity and surface hydrophilicity. The results showed that highly salt-tolerant microalgal cells (Dunaliella salina, Nannochloropsis sp.) had significantly higher tendencies to attach on the gelatin-modified PHEMA hydrogel compared with the freshwater B. braunii colonies; embedded within an extracellular matrix mainly made of hydrophobic components, which displayed better attachment to the unmodified PHEMA hydrogels. CONCLUSION: The proposed PHEMA hydrogels are easily-manufactured and highly durable materials with the hydrogel disks still retaining their integrity after several years when in contact with a liquid. PHEMA disks also have the benefits of having adjustable porosities by changing the composition of the polymerization mixture, and modifiable surface properties by simply binding various synthetic or natural molecules on their surfaces, which can bring several new opportunities for harvesting various microalgal cells with different surface morphologies and chemical compositions.